2011
DOI: 10.1074/jbc.m111.258467
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Relationships between the Lectin and Arm Domains of Calreticulin

Abstract: Calreticulin and calnexin are key components in maintaining the quality control of glycoprotein folding within the endoplasmic reticulum. Although their lectin function of binding monoglucosylated sugar moieties of glycoproteins is well documented, their chaperone activity in suppressing protein aggregation is less well understood. Here, we use a series of deletion mutants of calreticulin to demonstrate that its aggregation suppression function resides primarily within its lectin domain. Using hydrophobic pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
51
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 47 publications
1
51
0
Order By: Relevance
“…The ability of these chaperones to suppress client protein aggregation appears to be due in part to their sequestration of glycoprotein folding intermediates between the globular lectin domain and the flexible extended arm domain. This is suggested on the basis of FRET experiments using probes within the two domains (22) as well as arm domain truncation mutants that exhibited reduced abilities to suppress aggregation in vitro (23,24).…”
Section: Membrane-bound Calnexin (Cnx)mentioning
confidence: 99%
See 4 more Smart Citations
“…The ability of these chaperones to suppress client protein aggregation appears to be due in part to their sequestration of glycoprotein folding intermediates between the globular lectin domain and the flexible extended arm domain. This is suggested on the basis of FRET experiments using probes within the two domains (22) as well as arm domain truncation mutants that exhibited reduced abilities to suppress aggregation in vitro (23,24).…”
Section: Membrane-bound Calnexin (Cnx)mentioning
confidence: 99%
“…Substrates-Previously, we showed that Crt suppresses the aggregation of non-glycosylated client proteins through a polypeptide binding site that resides within its globular lectin domain but at a site distinct from the site of oligosaccharide binding (24). To localize the polypeptide binding site more precisely, we turned to our crystal structure of the mouse Crt lectin domain (4) and identified four surface-exposed hydrophobic patches at locations removed from the lectin site that could potentially mediate aggregation suppression (Fig.…”
Section: Identification Of the Polypeptide Binding Site On Calreticulmentioning
confidence: 99%
See 3 more Smart Citations